Using the Approach of Reengineering the Management Process to Improve Performance The Case Study of the Federation of Egyptian Industries - Abdel Wahab, Yasser (The Arab Journal of Administration, 2018)
The study aims at clarifying the concept of the approach of reengineering the management process and realizing its role in improving the performance of Egyptian industrial enterprises and how much it can be benefited from in the light of the current challenges by applying on the Federation of Egyptian Industries and the its chambers of industry. To achieve this goal, the researcher conducted a field study on a sample of respondents (Chairmen of the chambers of industry, members of boards of directors, general managers of those rooms) as the most knowledgeable and the most associated with the management process. That is because these groups play an important role in the formation of the desired culture, as well as possessing the ability to objectively answer the questions of the study, included in the survey. This could enable the emergence of positive results in terms of the seriousness of the answer, the factor of experience and professional knowledge. This could enable the researcher to highlight various angles associated with the subject of study. The study tested the following two hypotheses: First hypothesis (H1): There are statistically significant moral level relationship a ≤ 0.05 among the demographic factors of the sample respondents. The second hypothesis (H2): There are statistically significant moral level relationship a ≤ 0.05 between the application of the respondents to the approach of the reengineering the management process and the improvement of performance of the Egyptian industrial enterprises. The findings of the study resulted in the acceptance of the study hypothesis, and the presence of a positive impression among the respondents about the approach of the reengineering the management process. The study showed a range of results, notably includes the following: The Egyptian Industries Union and its industrial chambers, have already begun applying the approach of reengineering the management process since quite some time to prepare to cope with change and development. It actually has entered into agreements with many international organizations related to improving the performance of the Egyptian industrial enterprises. There is a strong relationship between the application of the approach of reengineering management process and performance improvement. This underscores the interest of the Federation of Egyptian Industries and its industrial chambers – the study society – in this approach to contribute to the process of developing and improving performance. The application of the approach of reengineering the management process represents (68.7%) of the reasons for improving performance. It hasn’t been clear that there are essential differences between the Federation of Egyptian Industries and its Industrial Chambers about the degree of importance of applying the approach of reengineering the management process in improving performance.